Perkembangan Tasawuf di Nusantara - Barlian Fajri (Sekolah Tinggi Ilmu Tarbiyah Tihamah, 2023)
Sufism as an integral part of Islamic thought has been known to the people of Indonesia for centuries, paralleling the development of Islam at the end of the 12th century. Although various theories have been raised to determine the beginning of the arrival of Islam, the end of the 12th century can be used as the starting point for the development of Sufism in Indonesia. Archipelago. This research is a type of literature research, in which researchers conduct in-depth studies by reading, researching, and analyzing various types of relevant literature. The mass spread of Islam in Indonesia, especially since the 16th century, was colored by the role of the Sufis. From these Sufi teachers who were directly initiated in the Middle East, the tarekat then experienced a spread through their students, to all regions of Indonesia. Sufi figures who influenced the development of Sufism in Indonesia